Futuros: da descoberta pela consciência à exposição midiática - Pereira Filho, Bernardo de Aguiar (2012)
The present research aims at determining how images of the future were established through means of communication and which processes were involved in building these scenarios. Our goal is to recognize how this production may be committed to interests or ideas of what the progress is, and if they are part of a hegemonic domination of the capitalism and the information produced in the United States and in Europe. Based on faster and faster technological progress and scientific advances, visionaries and specialists have tried, along the Twentieth Century, to anticipate the form and manner in which we would live in the future. The means of communication were responsible for catalyzing and promoting this (essentially American) imagination to the rest of the world through newspapers and magazine articles, science fiction literature and movies. Somehow, this repertoire has permeated our ideas of the future and has influenced the construction of the present, making us seek for the materialization of these predictions. We notice that mainly along the second half of the 20th Century, images of the future start to be substituted in a faster pace due to new discoveries or technological inventions. The question that guides us is: What are the processes involved in building the future and how does the media dissemination influence our vision of the world? Methodologically, as a case study we chose the episode The Body , of the 2057 documentary aired by the pay TV channel Discovery Channel (2007), by examining its content that mixes testimonials of scientists with drama narratives and at the same time uses science fiction movies techniques. In the documentary, the theoretical physicist Michio Kaku tries to predict how our lives the body, the cities, the world will be in fifty years from now, suggesting the possibility of immortality. We will map out different representations of the future introduced by the media since last century up to the present moment based on the studies of theorists of the area such as Thomas Lombardo, Wendell Bell, Richard Slaughter and Lawrence Samuel. We will use the theory of signification according to the interpretative model proposed by Jakob Uexküll and Jorge Vieira, to analyze how these signs are perceived